Regeneration after blood loss and acute inflammation proceeds without contribution of primitive HSCs - Munz, Clara M.; Dressel, Nicole; Chen, Minyi; Grinenko, Tatyana; Roers, Axel; Gerbaulet, Alexander (Blood, 2023)
Hematopoietic stem cells (HSCs) are the ultimate source of blood and immune cells, and transplantation reveals their unique potential to regenerate all blood lineages lifelong. HSCs are considered a quiescent reserve population under homeostatic conditions, which can be rapidly activated by perturbations to fuel blood regeneration. In accordance with this concept, inflammation and loss of blood cells were reported to stimulate the proliferation of HSCs, which is associated with a decline in their transplantation potential. To investigate the contribution of primitive HSCs to the hematopoietic stress response in the native environment, we use fate mapping and proliferation tracking mouse models. Although primitive HSCs were robustly activated by severe myeloablation, they did not contribute to the regeneration of mature blood cells in response to prototypic hematopoietic emergencies, such as acute inflammation or blood loss. Even chronic inflammatory stimulation, which triggered vigorous HSC proliferation, only resulted in a weak contribution of HSCs to mature blood cell production. Thus, our data demonstrate that primitive HSCs do not participate in the hematopoietic recovery from common perturbations and call for the reevaluation of the concept of HSC-driven stress responses.
Gesehen am 13.07.2023